Association of healthcare system factors with childhood leukemia mortality in Peru, 2017–2019: A population-based analysis. (September 2021) - Valcarcel, Bryan; Murillo, Franco; Torres-Roman, J. Smith
Highlights: Peru has high childhood leukemia mortality rates. Healthcare system factors related to childhood leukemia mortality varied by leukemia subtype. Prolonged travel time to a medical center is associated with childhood leukemia mortality. Our analysis suggests healthcare capacity disparities within Peruvian provinces. Peru should strengthen the decentralization process of leukemia cancer-directed therapy. Abstract: Background: Childhood leukemia mortality is expected to increase in certain developing Latin American countries by 2030. The development of tailored public health interventions could benefit by understanding the role of healthcare system factors. Therefore, we aimed to evaluate the area-level association of healthcare system factors with leukemia mortality among Peruvian children aged 0–19. Methods: We abstracted province-level death counts from the National Death Registry Information System database between 2017 and 2019. Continuous factors were dichotomized by their median. We fitted multivariate quasi-Poisson regression models for all leukemia and stratifying by subtypes of leukemia. Results: From 2017 to 2019, 755 leukemia deaths were reported. Healthcare system factors associated with mortality varied by leukemia subtype. In lymphoid leukemia, a prolonged travel time to a healthcare facility (RR: 1.26, 95 % CI: 1.01−1.58), a high density of primary care physicians (RR: 1.57, 95 % CI: 1.25−1.97), and a high density of hospitals (RR: 1.64, 95 % CI: 1.23−2.20) were related to mortality. In myeloid leukemia, only a high density of hospitals (RR: 1.76, 95 % CI: 1.06−3.01) was associated with mortality. Conclusion: The province-level healthcare system factors related to mortality varied by leukemia subtype on children aged 0–19. The association found in provinces with a high density of primary care physicians or hospitals suggests a disparity in case identification between the areas with better and worse healthcare capacity. Higher mortality rates in provinces with prolonged travel time to a healthcare facility indicate a centralization of cancer-directed treatment and difficulties with its distribution. Policy summary: To prevent childhood leukemia deaths, we highlight the need to strengthen the public health system through policies that enhance the distribution of leukemia treatment to locations far away from medical centers. Strengthening the supply, distribution, and adherence to leukemia cancer-directed treatment should be a public health priority for Peru.